Society/nature relation and environmental in semiarid cearense - Cabral, Rosiane Muniz; Sousa, Maria Losângela Martins de; Oliveira, Vládia Pinto Vidal de (Revista Hipótese, 2017)
The objectve of this article is to reflect about the complex relation between society and nature and the process of ambiental degradation in the Ceará’s semi-arid region. In front of this perspective, it is necessary to adopt environmentall planning measures in order to minimize that problem. The metodology adopted to the present article refers to geocartographic and litterature surveys and on site researches. The process of Ambiental Education can act as a tool to face that problematics.
Keywords: Desertification; Environmental education; Geosystems; Complexity Theory